Normal variability within a collegiate athlete sample: A rationale for comprehensive baseline testing. Issue 7 (3rd October 2021) - Fallows, Robert R.; Mullane, Audrina; Smith Watts, Ashley K.; Aukerman, Douglas; Bao, Yuqin
Abstract: Objective: Sport-related concussions continue to garner attention as research emerges about the effects of these injuries. Many have advocated for cognitive baselines; however, there is no uniform practice of neuropsychological baseline testing at the collegiate level leading to variance in administration and interpretation. Continuing clarification on best practices is essential for the field, especially considering previous research highlighting normal variability on cognitive tests in other populations, but also the need for separate normative sources for those with attention and learning problems. This study aimed to evaluate the range of normal variability in a diverse sample of collegiate athletes administered a traditional neuropsychological baseline. Method: Neuropsychological baseline measures were collected on 236 Division 1 University student athletes over 4 years. Frequency of scores that fell at 1, 1.5, and 2 or greater standard deviations were reviewed. Student athletes were further evaluated for likelihood of factors which could impact results (i.e. Attention-Deficit/Hyperactivity Disorder [ADHD], Specific Learning Disorder [SLD], and psychiatric distress). Results: The results demonstrated high rates of variability in most test scores for the collective sample. Student athletes at risk for ADHD, SLD, and/or psychiatric distress appeared to demonstrate a higher degree of variability relative to individuals with minimal risk. Conclusion: Baseline evaluation data revealed the presence of normal variability in a student athlete population. Left unrecognized, this can lead to errors in clinical recommendations given the nature of concussion. Certain individuals have risk factors which may increase the range of variability, and this should be explored further in future research.